A Rare Case of an Early Postoperative Obstructive Ileus in a Young Female Patient due to a Residual Trichobezoar Mass - P. Christopoulos; S. Ross-Thriepland; H. McCarthy; C. S. Day; W. Sasi (Case Reports in Surgery)
Trichobezoar is a rare cause of small bowel obstruction, whereby a mass forms most commonly in the stomach and duodenum of young females, from ingestion of hair, a condition known as trichophagia. We present a case of recurrent small bowel obstruction due to a residual hair mass that was removed surgically in a young female patient who had a laparotomy and gastrotomy for removal of a large gastric trichobezoar just two weeks prior to the current admission. This case illustrates the importance of a thorough inspection of the whole bowel to ensure that no residual bezoars remain after surgery.